Human recombinant granulocyte-macrophage colony-stimulating factor increases cell-to-cell adhesion and surface expression of adhesion-promoting surface glycoproteins on mature granulocytes. - Arnaout, M A (1986)
Human granulocyte-macrophage colony-stimulating factor (GM-CSF) has been shown to inhibit migration of mature granulocytes and to enhance their antibody-dependent cellular cytotoxicity. We found that human recombinant GM-CSF also enhanced granulocyte-granulocyte adhesion and increased by two- to threefold the surface expression of Mo1 and LeuM5 (P150, 95), two members of a family of leukocyte adhesion molecules (Leu-CAM). Increased Mo1 surface expression occurred within 15 min at 37 degrees C and was maximal at the migration inhibitory concentration of 500 pM. One-half maximal rise in the expression of Mo1 on the cell surface occurred at 5 pM. The chemotactic peptide f-Met-Leu-Phe produced a comparable rise in surface Mo1 with one-half maximal expression occurring at 7 nM. Both GM-CSF and f-Met-Leu-Phe produced optimal granulocyte-granulocyte adhesion at 500 pM and 100 nM, respectively. This adhesion-promoting effect induced by either stimulus was inhibited by a mouse monoclonal antibody directed against Mo1 antigen. These data indicate that GM-CSF promotes cell-to-cell adhesion, presumably through enhanced expression of leukocyte adhesion molecules. This mechanism may explain, in part, the known effects of GM-CSF on the function of mature granulocytes.